FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA DALAM PEMILIHAN PRODI PENDIDIKAN SOSIOLOGI FISE UNY - Fanani, Arif; Badruddin, Badruddin (JIEGC Journal of Islamic Education Guidance and Counselling, 2020)
The purpose of this research is based on the background of the Sociology Education Study Program at YSU which is a new study program. Sociology Education Study Program which was in the Department of Education in 2004. From year to year there has been an increase in the enthusiasm of UNY students who choose the Department of Sociology Education Study Program. Based on the background of the problem, This study only wants to find out what factors influence students on the selection of the 2018 Class of Sociology Education Study Program. This research method uses a qualitative approach. It is defined as a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. The results of this study are internal factors (intrinsic / internal), which is a rational choice in achieving these goals. In this study, internal factors dominate more, and students do have the interest and aspirations to continue to higher education, especially the Sociology Education Study Program. External factors (extrinsic / external), namely family, school, community and the environment, which provide encouragement or information for individuals on the selection of the Sociology Education Study Program. This factor in this study is only a supporter. Interest is a positive attitude towards learning